Guía de manejo inicial de las lesiones por extravasación - Meneses R., Pablo; Huerta M., Camilo; Venegas N., Josefa; Albornoz G., Claudia; Benítez S., Susana; Domínguez C., Carlos; Erazo C., Cristián; Sepúlveda P., Sergio (Revista Hospital Clínico Universidad de Chile, 2024)
No abstract available